Impact of pre-stroke cognitive decline on rehabilitation effectiveness and cognitive-functional status of patients in the acute period of ischemic stroke - Anastasya M. Tynterova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Summary. The aim was to assess the influence of premorbid cognitive deficit on the effectiveness of rehabilitation using VR technologies and cognitive-functional status of patients in the acute period of ischemic stroke based on statistical methodology. Materials and methods: 120 patients diagnosed with ischemic stroke were examined. The IQCODE questionnaire was used to identify the patient’s cognitive decline before and the Pandas and SciPy libraries. Results: all patients had a multifunctional type of cognitive impairment with a predominant decline in the areas of executive function, memory, speech and perception. Patients of the 2nd group had a more pronounced deficit in the areas of constructive praxis, episodic memory, semantic information processing and perception. Assessment of the dynamics of cognitive impairment during therapy revealed a significant improvement in memory loss (p=0, 0034), executive dysfunction (p<0.0001) and attention impairment (p=0.0001) in patients of 1st group and regression cognitive deficit in almost all cognitive areas in patients of 2nd group. Factors impeding rehabilitation in 1st group of patients were attention (r = -0,325) and perceptual disorders (r = -0,425); in 2nd group: semantic aphasia (r = -0,425), constructive apraxia (r = -0,325), speech impairment (r = — 0,375), object agnosia (r = -0,323) and IQCODE (r = -0,395). Conclusion: pre-stroke cognitive impairments are predictors of the development and progression of post-stroke cognitive deficits and reduce the possibilities of rehabilitation and cognitive recovery. The introduction of IQCODE in the diagnosis of cognitive dysfunction in the acute period of ischemic stroke is a useful tool in predicting the course and development of cognitive deficit and studying the prospects of rehabilitation programmes using VR technologies in patients with pre-stroke cognitive impairment.